Phenotypic characterization of Neisseria meningitidis strains isolated from invasive meningococcal disease in Brazil from 2002 to 2017. Issue 1 (10th January 2020) - Gorla, Maria Cecília; Brandao, Angela Pires; Pinhata, Juliana Maira Watanabe; de Moraes, Camile; Pereira, Gabriela; Lemos, Ana Paula
Abstract : Introduction . Invasive meningococcal disease (IMD) has a high rate of fatality and may cause severe clinical sequelae. Over the years, the epidemiology of IMD has changed significantly in various regions of the world, and laboratory surveillance of this disease is important for mapping epidemiologic changes. Aim. To perform phenotypic characterization of Neisseria meningitidis strains isolated from invasive disease in Brazil from 2002 to 2017, as a complementation of the data obtained in the period of 1990–2001. Methodology . In total, 8, 689 isolates sent to Adolfo Lutz Institute confirmed as N. meningitidis by conventional methods were serogrouped by slide agglutination against MenA, MenB, MenC, MenE, MenW, MenX, MenY and MenZ; serotyped and serosubtyped by a whole-cell dot-blotting assay with monoclonal antibodies. Results . The isolates were sent from all regions of Brazil, and the southeast region was responsible for the largest number of isolates (57.2 %). Overall, the total sample ( n =8, 689) was represented by serogroups C ( n =4, 729; 54.4 %), B ( n =3, 313; 38.1 %), W ( n =423; 4.9 %), Y ( n =203; 2.3 %), X ( n =5; 0.1 %) and others ( n =16; 0.2 %). A shift in the prevalence of serogroups was observed in 2006, when serogroup C became the most prevalent (65.5 %), surpassing the serogroup B (21.9 %). The main isolated phenotypes were C:23:P1.14–6; B:4, 7:P1.19, 15; W:2a:P1.5 and W:2a:P1.5, 2. Conclusion . The data show an important change in the distribution of meningococcal serogroups, serotypes and subtypes occurring during 2002–2017. A continuous laboratory-based surveillance provides robust information to implement appropriate strategies to IMD control.